Response Prediction to Concurrent Chemoradiotherapy in Esophageal Squamous Cell Carcinoma Using Delta-Radiomics Based on Sequential Whole-Tumor ADC Map - An, Dianzheng; Cao, Qiang; Su, Na; Li, Wanhu; Li, Zhe; Liu, Yanxiao; Zhang, Yuxing; Li, Baosheng (Frontiers in Oncology, 2022)
Purpose: To investigate the association between the radiomics features (RFs) extracted from whole-tumor ADC map during the early treatment course and response to concurrent chemoradiotherapy (cCRT) in patients with Esophageal Squamous Cell Carcinoma (ESCC). Methods: Patients with esophageal squamous cell carcinoma who received concurrent chemoradiotherapy were enrolled in two hospitals. Whole-tumor ADC values and RFs were extracted from sequential ADC maps before treatment, after 5th radiation and after 10th radiation and the changes of ADC values and RFs were calculated as relative difference between different time point. RFs were selected and further imported to Support Vector Machine classifier for building a radiomics signature. Radiomics signatures were obtained from both RFs extracted from pretreatment images and three sets of delta-RFs. Prediction models for different responders based on clinical characteristics and radiomics signatures were built up with logistic regression. Results: Patients (n=76) from the hospital 1 were randomly assigned to training (n=53) and internal testing set (n=23) in a ratio of 7 to 3. In addition, to further test the performance of the model, data from another institute (n=17) was assigned to the external testing set. Neither ADC values nor delta-ADC values were correlated with treatment response in the three sets. It showed a predictive effect to treatment response that the AUC value of radiomics signature built from delta-RFs over first 2 weeks was respectively 0.824, 0.744 and 0.742 in the training, the internal testing and the external testing set. Compared with the evaluated response, the performance of response prediction in internal testing set was acceptable (p = 0.048). Conclusions: The ADC map-based delta-RFs during early course of treatment were effective to predict response to cCRT in patients with ESCC.